Synthesis, Characterization and Biological activities of 2-Amino-3-Methyl pyridine New Dithiocarbamate metal complexes - Khajavali, S.; Jayaraju, A.; Sreeramulu, J. (Journal of Drug Delivery and Therapeutics, 2019)
Dithiocarbamates are a class of sulfur-based metal-chelating compounds with various applications in medicine. A new series of new transition metal [Cu(II), and Ni(II)] complexes of dithiocarbamates were synthesized from 2-Amino-3-Methyl pyridine and Carbon disulfide and further characterized. The investigation of these complexes confirmed that the stability of metal–ligands coordination through, S&S,N atoms as bidendate chelates.. It is necessary to understand the binding properties in developing new potential Protein targeting against neurological disorders. Keywords:2-Amino-3-Methylpyridine,MetalComplexes,Dithiocarbamates,neurological disorders.